Design of a single-sided axial flux PM in-wheel electric vehicle machine with non-overlap stator windings - Kierstead, Harold Junior (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.